Aesthetic Perception and Empathy in Vasily Seseman’s Aesthetics - Jonkus, Dalius (Problemos, 2014)
The aim of this paper is to analyse Vasily Seseman’s conception of empathy. Seseman, similarly to Moritz Geiger, draws a parallel between the perception of aesthetic expressions and the other expressions of a person’s perception. According to Seseman, to understand another person’s spiritual life it is unnecessary to rely on deductions by analogy, like traditional theories claim. Expression has a common trait that meaning lives in it. That is why expressions do not have to be recognized in a way that we would like to reconstruct beyond their harboured meanings. Aesthetic depiction destroys opposition between sensible, material, bodily principle and the non-sensible, spiritual principle. Seseman states that empathy cannot be explained relying on the theory of analogy or the concept of psychological projection. The former presupposes a radical separation and confrontation between the subject and object. Seseman states that empathy is important to aesthetic perception because it is based on the expressive forms of the world and the correlation between their dynamics and movements of perception. To have empathy means to feel oneself together with others, to feel the others in connection with yourself. The dynamics of the world’s expressions directly reveal liveliness which pulls in the bodily perceptive subject with all of his senses as a whole. Echoing feelings are experienced not through the distance of visual sight, but through direct and contagious vibrations of bodily contact. The connection of the primordial perceived world and its perception reveals itself not on the mental, but a sensuous plane. That is why aesthetic feelings are better expressed not by the depiction of objects, but the creation of dynamic atmosphere of lines, colours, sounds. Diving into this vital dynamic is possible if the perceiving subject abstains from his pragmatic interests and habits and attains the attitude of aesthetic contemplation.
Keywords: Seseman; phenomenology; aesthetics; empathy; perception; expression; feeling